Functional Outcome of Single-Stage Reconstruction for the Multi-Ligament Injuries of the Knee - Hamal, Bhadra; Karmacharya, Mahesh; Bhattachan, Sijan; Hamal, Pawan Kumar (Journal of Nepal Health Research Council, 2025)
Background: Multi-ligament injuries of the knee are rare injuries that can cause significant impairment of the knee function. There is controversy in the treatment regarding staged versus single-stage surgery. This study was performed to assess the outcome of the single-staged reconstruction of the multi-ligament injury of the knee.Methods: This prospective observational study was done from January 15, 2022 to January 14, 2023. The outcome was analyzed by comparing the preoperative and 12-month postoperative Visual Analog Scale score, Lysholm Score, and International Knee Documentation Committee Score.Results: The mean age of the patients was 28.35 years. among 12 patients 9 were male and 3 were female. Single-staged multi-ligament reconstruction was done in all the cases. The Lysholm score was improved from preoperatively 36.42 ± 1.46 to 95.36 ± 2.84, IKDC score was improved from 24.38 ± 1.64 to 93.86 ± 3.14, VAS score 8.14 ± 1.44 to 0.40 ± 0.60 at 12 months postoperative follow-up which all came to be clinically significant with p-value < 0.001.Conclusions: Single-stage multi-ligament reconstruction of the knee is an effective method of treatment and has excellent outcomes.Keywords: Multi-ligament injury; reconstruction; single-stage.